Transcriptomic Study of Porcine Small Intestine Epithelial Cells Reveals Important Genes and Pathways Associated With Susceptibility to Escherichia coli F4ac Diarrhea - Augustino, Serafino M. A.; Xu, Qinglei; Liu, Xueqin; Liu, Lei; Zhang, Qin; Yu, Ying (Frontiers in Genetics, 2020)
Background: Diarrhea represents one of the most frequent major problems during piglets’ neonatal and post-weaning periods leading to tremendous economic losses in the swine industry. Enterotoxigenic Escherichia coli (ETEC) strain is regarded as the most important cause of diarrhea in piglets. However, some pigs are naturally resistant to diarrheal infection, because no F4 receptors (F4R) on their small intestine epithelial cells that allowing F4 fimbriae attachment. Thus, our study characterized a complete transcriptome of small intestine epithelial cells of Large White piglets using RNA-Seq. The aim of the study was to identify differentially expressed genes (DEGs) and important pathways involved in diarrhea resistance/susceptibility in piglets and provide molecular tools for genetic improvement of diarrhea resistance trait in swine. Methods: A total of 8 samples of small intestine epithelial cells obtained from Large White piglets less than 2 months used in this study were selected on the basis of two criteria. One was the adhesion phenotype to F4ac fimbriae of Enterotoxigenic Escherichia coli (ETEC-F4ac), and the other was the comparison of ITGB5 SNP (C>T) genotype sequences across all the samples. The samples were then divided into two groups, non-adhesive with CC genotype (resistant, n = 4) and adhesive with TT genotype (susceptible, n = 4). Results: More down-regulated DEGs (p < 0.05, FC > 2) were detected in the comparison of non-adhesive vs. adhesive small intestine epithelial cells in the present study. The down-regulated DEGs (including HCN4, MYLK, KCNMA1 and KCNMB1) were involved in two pathways associated with diarrhea which could be behind the susceptibility phenotype manifested in adhesive small intestine epithelial cells. While up-regulated DEGs were mostly engaged in many immune response-related pathways. This might have enhanced the resistance to ETEC-F4 diarrhea observed in non-adhesive small intestine epithelial cells. Conclusion: The findings of the current study could be used as molecular markers in the quest for resistance/susceptibility phenotype to ETEC-F4ac induced diarrhea in swine. Finally, our study provided a suitable ground foundation for further validation studies at a later time using molecular genetic techniques such as gene silencing and knockout studies.